2017
DOI: 10.1105/tpc.17.00397
|View full text |Cite
|
Sign up to set email alerts
|

A Plastid Phosphatidylglycerol Lipase Contributes to the Export of Acyl Groups from Plastids for Seed Oil Biosynthesis

Abstract: The lipid composition of thylakoid membranes inside chloroplasts is conserved from leaves to developing embryos. A finely tuned lipid assembly machinery is required to build these membranes during development. Contrary to thylakoid lipid biosynthetic enzymes, the functions of most predicted chloroplast lipid-degrading enzymes remain to be elucidated. Here, we explore the biochemistry and physiological function of an Arabidopsis thylakoid membrane-associated lipase, PLASTID LIPASE1 (PLIP1). PLIP1 is a phospholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 65 publications
6
70
0
Order By: Relevance
“…Thus, based on our analysis, which is independent of the 16C/ 18C rule, a substantial fraction of PG is derived from the ER. It should be noted that the majority of plastid PG contains an unusual C16 fatty acid at its sn-2 position, 16:1 D3t , making it the target of a specific lipase, PLIP1 (Wang et al, 2017). The partial ER-origin of plastid PG in Arabidopsis is likely to be obscured using traditional approaches by specific acyl group remodeling of chloroplast PG, but is clearly apparent in the Myc-D6D transgenic lines using the 'tag and track' approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, based on our analysis, which is independent of the 16C/ 18C rule, a substantial fraction of PG is derived from the ER. It should be noted that the majority of plastid PG contains an unusual C16 fatty acid at its sn-2 position, 16:1 D3t , making it the target of a specific lipase, PLIP1 (Wang et al, 2017). The partial ER-origin of plastid PG in Arabidopsis is likely to be obscured using traditional approaches by specific acyl group remodeling of chloroplast PG, but is clearly apparent in the Myc-D6D transgenic lines using the 'tag and track' approach.…”
Section: Discussionmentioning
confidence: 99%
“…A second piece of evidence is the observation of SDA and 16:3 acyl groups in the same MGDG molecule as the first acyl group originates in the ER and the second in the plastid (Figure 4c). Acyl editing has been described for PC at the ER (Bates et al, 2007) or the plastid envelope (Tjellstrom et al, 2012), for plastid MGDG in Chlamydomonas (Li et al, 2012), and recently for plastid PG during seed development (Wang et al, 2017). Each of these reactions are proposed to contribute to the export of acyl groups from the plastid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For lipid breakdown, the Arabidopsis thaliana genome encodes hundreds of predicted lipases; different lipases cleave at different positions on the lipid and release fatty acids that can be oxygenated and converted into other compounds, including JA, by various enzymes. The authors had previously identified PLASTID LIPASE1 (PLIP1), which localizes to the chloroplast and participates in seed oil production (Wang et al, 2017). Here, they extend their studies to the PLIP1 homologs PLIP2 and PLIP3.…”
mentioning
confidence: 72%
“…Most of the following work focused on the transfer of lipid and PUFA from the ER to the chloroplast, establishing the idea that the reverse transport was negligible (Miquel & Browse, 1992; Li, N et al ., 2016). Nevertheless, the recent characterization of two Arabidopsis plastid lipases mutants highlighted that plastidic PUFA indeed contributed to PUFA remodelling of extraplastidic lipid (Wang et al ., 2017; Higashi et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%